KEMAMPUAN MENUNJUKKAN KARAKTER TOKOH DALAM DRAMA MENGGUNAKAN MODEL STORYTELLING: SEBUAH PENELITIAN KUASI EKSPERIMEN - Urmila Sari; Achmad Yuhdi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Students have difficulty in learning to play one of the characters in a drama. This can be seen from the low scores of students in the ability to play one of the characters in a drama, the lack of student interest in learning drama, students still seem not confident in playing the character in the drama in class, and the learning model used is not appropriate. The purpose of this study was to find out (1) To find out how the ability to play one of the characters in a drama is for class XI students of SMK Negeri 11 Medan without using the Storytelling learning model; (2) To find out how the ability to play one of the characters in a drama is for class XI students of SMK Negeri 11 Medan using the Storytelling model; (3) To find out how the Storytelling model influences the ability to play one of the characters in a drama for class XI students of SMK Negeri 11 Medan. This study used a quasi-experimental method with a post-test two group design model. The results of the study showed that 1) The ability of class XI students of SMK Negeri 11 Medan in playing one of the characters in a drama without using the Storytelling model is included in the good category with an average value of 71.50. 2) The ability of students of class XI SMK Negeri 11 Medan in showing one of the characters in a drama using the Storytelling model is included in the very good category with an average value of 84,48. Based on the t-test, with a significance level value of α = 0.05 and n = 30, a t-table value of 2.04 was obtained. Therefore, it can be concluded that t-count> t-table, which is 5.275> 2.04. This proves that there is a significant influence of the use of the Storytelling model on the ability to show one of the characters in the drama.